Evaluating the Impact of Preclinical and Clinical Exposure to the Pediatric Pulpotomy Procedure on Confidence Among Senior Dental Students: An Analytical Survey Study - Alzain I; Albqmi SS; Alkatheeri SM (Clinical, Cosmetic and Investigational Dentistry)
Ibtesam Alzain,1 Shouq Sultan Albqmi,2 Sadeem Mohammed Alkatheeri2 1Pediatric Dentistry Department, King Abdulaziz University, Jeddah, Saudi Arabia; 2King Abdulaziz University, Jeddah, Saudi ArabiaCorrespondence: Ibtesam Alzain, Pediatric Dentistry Department, King Abdulaziz University Faculty of Dentistry, P.O. Box: 80209, Jeddah, 21589, Saudi Arabia, Tel +966542001234, Fax +9666403316, Email ioalzain@kau.edu.saPurpose: This study evaluated senior dental students’ confidence in their knowledge and clinical skills in performing pulpotomy procedures on primary molars based on the number of procedures performed on pediatric patients and/or extracted primary teeth.Methods: An electronic survey was validated and modified from the National League of Nursing (NLN) questionnaire and was used to assess the student’s satisfaction with past learning and self-confidence in performing pulpotomy on pediatric patients and primary extracted teeth. The questionnaire comprised 29 questions across six sections outlining various clinical experience and knowledge acquisition aspects. The target sample was senior dental students enrolled at a governmental dental school during the 2023– 2024 academic year, which were 369 students who were recruited for this study. The association between knowledge and clinical experience of performing pulpotomies and self-confidence was analyzed using a chi-square test. The association between knowledge and practical/clinical experience and the competency grade was performed using an independent sample t-test and ANOVA (α = 0.05).Results: Of the targeted subjects, 215 responded to the questionnaire, yielding a response rate of 66.3%. A significant association was found between the number of procedures performed on pediatric patients and students’ confidence levels (p< 0.001), as well as between competency grades and confidence levels (p< 0.001). In contrast, the number of times they practiced pulpotomy on extracted teeth did not significantly affect their confidence level (p=0.381). No significant association existed between knowledge scores and confidence levels (p=0.869). Those who reported better learning experiences were more likely to report higher confidence levels (p< 0.001).Conclusion: The number of pulpotomy procedures performed on pediatric patients significantly impacted students’ confidence levels, while knowledge scores showed no correlation with confidence. A positive relationship between competency grades and confidence. These findings underscore the importance of practical training in enhancing both clinical skills and confidence in performing clinical procedures.Keywords: dentistry, dental procedures, confidence, dental interns, clinical experience, theoretical knowledge, pediatric dentistry